Effect Inulin Addition on The Proximate Content of Low Glycemix Index Growol Cookies - Puspita Mardika Sari; Desty Ervira Puspaningtyas; Silvia Dewi Styaningrum; Anita Nidyarini; Tirza Frelly Anita (Ilmu Gizi Indonesia, 2023)
Background: Growol is traditional fermented cassava which potentially developed as snack for diabetic patient. Previous study found that modification of growol cookies with addition of inulin were decreased glycemic index and glycemic load. However, information nutrition content of this modification were not known yet. Purpose: This study examined the effect of addition inulin on proximate content of growol cookies. Method: Observational laboratory of three formulas consists of addition with 5 gram inulin (A); 10 gram inulin (B); and control/ without inulin (C). Nutrition content of growol cookies were analyzed by using proximate analysis, consists of water and ash (thermogravimetri); protein (Kjeldahl); fat (Soxhlet); and carbohydrate (by difference). Data were analyzed using SPSS software with ANOVA followed LSD for ash, protein, and carbohydrate, while fat and water content were using Kruskal Wallis. Results: There were significant differences of proximat content between control group (growol cookies) and its modification (growol cookies with inulin addition) (p<0,001). Modification of growol cookies with inulin addition significantly decrease calorie (p<0,001) and fat (p=0,001) content, as well as increase protein content (p<0,001). Conslusion: Addition of inulin affected on decreased of calorie and fat content, also increased of water, ash, protein and carbohydrate content. Development and evaluation in scale up production were needed to fullfill the requirement for SNI standart of cookies.